OPTIMALISASI MASJID DESA KAJAN BLEGA BANGKALAN - Lutfianto (Jurnal Masyarakat Mengabdi Nusantara, 2022)
Abstract: Optimization of the village mosque of Kajan Blega Bangkalan. The problem formulation raised in this community service activity is Concerning with the weak understanding of mosque administrators towards the concept of efforts to prosper mosques and management the al-Mubarokah Kajan Blega Bangkalan mosque which is very urgent for part of the preaching of the people Islam. To find alternative solutions to the above, training was held Efforts to optimize and manage mosques at Masjid al-Mubarokah Kajan Blega Bangkalan. The objectives of this PKM activity are: 1. To equip mosque administrators towards the knowledge of Mosque Management. 2. Equip the Mosque Management as a preacher in a better change. 3. Improve knowledge and morals of society through mosque management that touches the heart the congregation The problem solving framework designed in PKM activities in the form of implementation of this training activity is: 1. Explanation of the concept of good mosque management theory with a philosophical basis followed by practice of finding the root of the problem according to conditions. 2. Design and implement training mosque management accompanied by the supervision and guidance of the administrators of the inner mosque planning activities to be carried out in the next year. 3. Evaluation of training results. Based on interviews, question and answer and direct observation during activities take place, this community service activity provides results: first, Increased knowledge and understanding of the congregation, second is to equip the Jama'ah as a missionary interpreter, the third is to improve knowledge and morals of the community, the formation of a ready mosque management preach